Frequency of mortality in stroke patients admitted in Ayub Teaching Hospital Abbottabad - Waheed, Sana; Mumtaz, Tayyaba; Javed, Muhammad Ali; Khan, Muhammad Ali (Indus Journal of Bioscience Research, 2025)
Background: Inpatient stroke mortality is a serious healthcare challenge worldwide with various causes for increased risk. The study seeks to explore the influence of different demographic, clinical, and comorbidity conditions on stroke hospital mortality, emphasizing the manner in which factors have an effect on the patient. Objective: To determine the frequency of inpatient mortality in stroke patients admitted in Ayub Teaching Hospital Abbottabad. Study Design: Descriptive, cross-sectional study. Duration and Place of Study: Conducted between August 2024 and February 2025 at the Department of General Medicine, Ayub Teaching Hospital, Abbottabad. Methodology: A total of 111 patients, aged 30–70 years, with a diagnosis of stroke were enrolled. Data collected included demographics, stroke type, comorbidities, and residential status. Inpatient mortality was defined as death occurring due to stroke after 24 hours of admission but before discharge. Statistical analysis was performed using IBM SPSS version 26, and a p-value of ≤ 0.05 was considered statistically significant. Results: The study found a 13.5% inpatient mortality rate. Mortality was higher in male patients and those from rural areas. Statistically significant associations were found between mortality and gender (p = 0.003), residential status (p < 0.001), socioeconomic status (p < 0.001), diabetes (p < 0.001), hypertension (p = 0.010), smoking (p < 0.001), and type of stroke (p < 0.001). Conclusion: Inpatient stroke mortality is significantly influenced by modifiable factors such as comorbid conditions (hypertension, diabetes, smoking), as well as demographic factors including gender, residential area, and socioeconomic status.